A social exchange approach to people's participation in watershed programs in Iran - Bagherian, Reza; Abu Samah, Bahaman; Abu Samah, Asnarulkhadi; Ahmad, Shamsuddin (EuroJournals, 2009)
The degree of popular participation in development programs is a major determinant of success or failure but the factors which make participation efforts successful still remained a mystery. Many studies have developed numerous and sometimes different views concerning to the dimensions of participation. Most of these literatures tends to be descriptive and rarely applies theory. This study was designed to analyze the people participation in Watershed Management Programs in Iran by using the framework of social exchange theory and determine the role of this theory in explaining people participate in Watershed Management Programs. In order to achieve to this goal, a cross sectional survey was design and utilized. The data for this study were gathered from 200 respondents which were randomly selected in three villages in August and September 2008 through personal interviews by using a questionnaire. Findings of study showed that there are significant relationship between exchange factors and level of people participation in watershed management programs in Iran. Multiple regression analysis discovered that exchange factors explained 33 percent of variation in the level of people participation in watershed management programs. This study found that social exchange theory is an appropriate perspective to explain level of people participation but participation is a complex issue and future researchers might use multiple perspectives for explaining participation.